Parasitology : (Cambridge iniversity press, 2002)
The papers in this volume examine the natural variations in parasites and their hosts, emphasizing the need for information on the nature and origins of their variations. All organisms vary genetically and phenotypically. This variability, when combined with the variety of interactions between parasites and their hosts, leads to the need to understand the practical significance of the variations possible. Variations in host fitness and/or parasite phenotypes can lead to altered disease rates and host mortality. They can also possibly lead to determining improved means of parasite control.